Volatile chemical composition of Colombian Piper gorgonillense Trel. & Yunck. essential oil and its repellent and fumigant activity against Tribolium castaneum Herbst (2020)
Essential oils (EOs) are mixtures of volatile organic compounds, mostly terpenes, from the secondary metabolism of plants. These oils exert various activities on insects that damage crops and cause losses worldwide for the economy and agriculture. Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) is one of the main pests causing the loss of a large amount of stored food. The objective of this study was to evaluate the volatile chemical composition of the essential oil from Piper gorgonillense Trel. & Yunck. and its repellent and fumigant activity on T. castaneum. The volatile composition was determined with gas chromatography coupled to mass spectrometry. The majority compounds found in the EO were b-caryophyllene (28.7%), a-copaene (13.5%), and d-cadinene (7.3%). The repellency percentages obtained were 78 and 90% at a concentration of 1% with exposure times of 48 and 72 hours, respectively. The fumigant activity refers to the insecticidal action that an essential oil vapor can have without coming into direct contact with insects; this was 100% at a concentration of EO 350 µg mL-1. The results showed that the P. gorgonillense EO had repellent and insecticidal properties for the biological control of T. castaneum.